MULTI-CHANNEL FRY COUNTER DESIGN USING OPTOCOUPLER SENSOR - Lazuardi Umar; Yanuar Hamzah; Rahmondia N Setiadi (Program Studi Fisika Universitas Negeri Jakarta, 2019)
This paper describes a design of a fry counter intended to be used by consumption fish farmer. Along this time, almost all the fry counting processes are counted by manual, which is done by human. It is requiring much energy and needs high concentration; thus, can cause a high mental and emotional exhaustion for the fry counting worker. Besides that, the human capability and capacity for counting the are limited to a low number. A fry counter design in this study utilizes a multi-channel optocoupler sensor to increase the counting capacity. The multi-channel fry counter counting system is developed as a solution to a limited capacity of available fry counter. This design uses an input signal extender system for the sensor. The design is based on the interrupt combiner to accommodate multi-channel sensor used. Besides, the transmitter beam's angle is adjusted to deal with the deflection due to water surface. From the experiment, multi-channel sensor can be implemented and high accuracy level could be obtained on the counting and channel number detection, therefore, this design can be implemented and could help farmers to increase the production capacity of consuming fish.